Energy harvesting by means of flow-induced vibrations on aerospace vehicles. (October 2016) - Li, Daochun; Wu, Yining; Da Ronch, Andrea; Xiang, Jinwu
Abstract: This paper reviews the design, implementation, and demonstration of energy harvesting devices that exploit flow-induced vibrations as the main source of energy. Starting with a presentation of various concepts of energy harvesters that are designed to benefit from a general class of flow-induced vibrations, specific attention is then given at those technologies that may offer, today or in the near future, a potential benefit to extend the operational capabilities and to monitor critical parameters of unmanned aerial vehicles. Various phenomena characterized by flow-induced vibrations are discussed, including limit cycle oscillations of plates and wing sections, vortex-induced and galloping oscillations of bluff bodies, vortex-induced vibrations of downstream structures, and atmospheric turbulence and gusts. It was found that linear or linearized modeling approaches are commonly employed to support the design phase of energy harvesters. As a result, highly nonlinear and coupled phenomena that characterize flow-induced vibrations are neglected in the design process. The Authors encourage a shift in the current design paradigm: considering coupled nonlinear phenomena, and adequate modeling tools to support their analysis, from a design limitation to a design opportunity. Special emphasis is placed on identifying designs and implementations applicable to aircraft configurations. Application fields of flow-induced vibrations-based energy harvesters are discussed including power supply for wireless sensor networks and simultaneous energy harvest and control. A large body of work on energy harvesters is included in this review journal. Whereas most of the references claim direct applications to unmanned aerial vehicles, it is apparent that, in most of the cases presented, the working principles and characteristics of the energy harvesters are incompatible with any aerospace applications. Finally, the challenges that hold back the integration of energy harvesting technologies in the aerospace field are discussed.